Comparison of efficacy of local hemostatic modalities in anticoagulated patients undergoing tooth extractions - Bajkin Branislav V.; Selaković Srećko D.; Mirković Siniša M.; Šarčev Ivan N.; Tadić Ana J.; Milekić Bojana R. (Vojnosanitetski Pregled, 2014)
Background/Aim. Patients receiving long-term oral anticoagulant therapy pose a clinical challenge during invasive dental procedures. The goal of this study was to compare different local hemostatic modalities after tooth extraction in patients receiving chronic Vitamin-K antagonist therapy. Methods. Totally 90 patients with International Normalized Ratio (INR) ≤ 3.0 requiring simple extraction of one or two teeth were randomized into three groups, 30 patients in each group. The patients with the mean INR value of 2.35 ± 0.37, in whom extraction wound was sutured comprised the group A. In the group B with the mean INR of 2.43 ± 0.4, local hemostasis was achieved by placing absorbable gelatin sponges into the wound without suturing. The group C consisted of the patients with the mean INR of 2.36 ± 0.34 in whom neither gelatin sponge nor suturing were used for providing local hemostasis. Bleeding was registered as an event if other than initial hemostatic measure was needed or additional oral surgeon intervention required. Results. The obtainded results show that 1 (3.3%) patient in the group A, 2 (6.7%) patients in the groups B and C manifested post-extraction bleeding. All cases of hemorrhage were easily solved with local hemostatic measures and all, except one case, were registered in the first two hours after the procedure until the dismissal. A difference between the groups was not statistically significant (χ2 = .42, p > 0.05). Conclusion. In therapeutically anticoagulated patients tooth extractions can be safely performed without altering the dose of anticoagulant medication if efficient local hemostasis is provided. In most cases, in patients with INR ≤ 3.0 after extraction of one or two teeth postoperative bleeding can be controlled with local pressure, without any additional local hemostatic measures.